Introduction of hands-on session using kolb experiential learning theory approach in teaching chemical instrumentation subject - Noorashikin M.S.,; Beh, S.Y.; Nur Atiqah N.W.N.,; Nurfaradilla M.N.,; Farhanini Y., (Penerbit Universiti Kebangsaan Malaysia, 2022)
Chromatography is a high-technology instrument that is widely used in the various in the various industry for decades. Hence, Science Bachelor Graduates’ that possesses ability to handle instrumentation are useful for their job nature. Learning approach that depends highly on lecture mode only enhance students’ knowledge on chromatographic techniques, but they might not possess skills on instruments handling. Therefore, the learning approach of Chemical Instrumentation Method (KKKR5833) subject using a Kolb Experiental Learning Theory are running by hybrid mode of lecture and hands-on teaching approach on chromatography. A total of 16 registered students were the respondent of this study. These students had been given lecture on the theoretical part of chromatography and later on, in agreement with the experiential learning theories, student will experience hands-on learning activity in HPLC laboratory session. Finally, a full report after completing the hands-on session for their overall experience in laboratory. Majority of the students that took this elective subject agreed that hands-on experience of using chromatography increases their knowledge on it and mastering the preparation of sample skill is very useful while 50% of the students put more effort in this subject and manage to score excellently. Moreover, majority graduate student express agreement that basic knowledge and skills on chromatographic is important before working and indicated that students with knowledge and skills on chromatographic instrumentation have higher chance of employment. This statement also agreed by respondent from industries. This prove that hands-on teaching and learning approach in laboratory using chromatography instrument able to enhance knowledge and student skills.